Recent advances in phase-locked loop based synchronization methods for inverter-based renewable energy sources - Haval Sardar Kamil; Dalila Mat Said; Mohd Wazir Mustafa; Mohammad Reza Miveh; Nasarudin Ahmad (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
Recently, researchers have shown an increased interest in renewable energy sources (RESs) to improve power quality, reliability and stability of the power system. However, RESs require proper control strategies to ride through grid disturbances and stay connected to the main grid for the stability contribution. Moreover, the control of them relies mainly on the synchronization algorithms to precisely detect the voltage phase angle, magnitude and frequency. Throughout the years, various synchronization schemes have been introduced and developed. In the renewable-based generation sources, the phase-locked loop (PLL) is a well-known technique for operating grid-tied power converters for the estimation of the synchronization information and grid voltage monitoring. This paper aims to provide a comprehensive review of the recently developed PLL algorithms for grid synchronization applications. At first, various estimation techniques are discussed. Then, a comparison between various PLLs and possible future works are recommended.